Risk Factors of Cervical Cancer and Comparison of 2 Methods for Cervical Cancer Screening - Pittayapreechakul, Keeratiya; Tantiseranee, Kaweewat; Srisawad, Piyapong; Manyoo, Benjamas (Health Science Journal of Thailand, 2022)
This research aimed to investigate risk factors of cervical cancer and to compare 2 methods of the screening tests: conventional pap smear (group 1) and HPV DNA test with liquid-based cytology (group 2), in 384 women who were screened at Somdejphrajaotaksin Maharaj hospital. There were 207 and 177 subjects in groups 1 and 2 repectively, based on the subjects’ choice. Through a Fisher’s exact test, alcohol drinking was associated with the positive result of cervical cancer screening in both groups. Through a Mantel-Haenszel test, the positive finding in group 2 was 6.79 times that in group 1 (95%CI: 1.49-31.07). The screening by HPV DNA test with LBC is likely to be more sensitive than that by CPS. Women with alcohol drinking should be prevented for cervical cancer. The replicated studies with larger sample size are suggested.